2004
DOI: 10.1017/s0266467404001397
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the dioecious understorey palm Chamaedorea radicalis in a Mexican cloud forest: pollination vector, flowering phenology and female fecundity

Abstract: The reproductive biology of the dioecious understorey palm Chamaedorea radicalis was investigated in order to identify the primary pollen vector and quantify the relationship between female fecundity and local neighbourhood sexual composition. The study was conducted in a montane mesophyll forest within the El Cielo Biosphere Reserve, Tamaulipas, Mexico. The species is considered vulnerable in Mexico and there are concerns about the sustainability of leaf harvest. We determined that wind is the primary pollen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 30 publications
3
44
0
Order By: Relevance
“…The difference in fruit production between the two populations studied here can be associated with intrinsic genetic characteristics or with environmental characteristics, such as availability of resources, nutrients in the soil, herbivory, competition and pollination (Crawley 2003). Reproduction can also vary between years (Miller 2002), and reproductive success is restricted by certain ecological factors, such as percentage of individuals reproducing, distance between reproductive individuals, availability of pollinators and climatic variations (Berry & Gorchov 2004). Only longer and more detailed studies can determine the effects of these factors in the reproduction of B. capitata.…”
Section: Productivity Of Fruitsmentioning
confidence: 99%
“…The difference in fruit production between the two populations studied here can be associated with intrinsic genetic characteristics or with environmental characteristics, such as availability of resources, nutrients in the soil, herbivory, competition and pollination (Crawley 2003). Reproduction can also vary between years (Miller 2002), and reproductive success is restricted by certain ecological factors, such as percentage of individuals reproducing, distance between reproductive individuals, availability of pollinators and climatic variations (Berry & Gorchov 2004). Only longer and more detailed studies can determine the effects of these factors in the reproduction of B. capitata.…”
Section: Productivity Of Fruitsmentioning
confidence: 99%
“…As the female flowers are rarely visited by the same insects as the male flowers, Listabarth concluded that pollen grains are transferred by wind and suggested the name 'insect induced wind pollination' for the mechanism. Mixed insect -wind pollination was also reported in Chamaedorea radicalis by Berry and Gorchov (2004) who found an increase in fruit-set from 3 % in bagged inflorescences to 23 % in palms in inflorescences that were treated to exclude insects, but allowing passage on wind-dispersed pollen grains from neighbouring individuals (bagging with nylon mesh, pore size approx. 1500 mm).…”
Section: Vectors Of Palm Pollinationmentioning
confidence: 61%
“…Three pollination ecological studies have been conducted on species in the first group: Chamaedorea pinnatifrons, C. radicalis and C. ernesti-augustii. The first two are primarily wind-pollinated (Listabarth, 1993a;Berry and Gorchov, 2004) whereas the third was reported to be insectpollinated (Hodel, 1992;Morgan, 2007). Otero-Arnaiz and Oyama (2001) revealed wind as the primary pollinating agent in C. alternans, a species belonging to the second group.…”
Section: Floral Protectionmentioning
confidence: 99%
“…and Chamaedorea radicalis Mart. (Piñero & Sarukhán 1982, Berry & Gorchov 2004. In A. mexicanum, when resources fail to reach a reproductive threshold, instead of producing a smaller inflorescence, it produce none at all , so the reproductive effort could be estimated by the number of inflorescence produced annually.…”
Section: Discussionmentioning
confidence: 99%
“…In the second group, the older plants experience fast reduction in growth and reproduction activities at the end of the life cycle (Chazdon 1992, Souza et al 2003. The third group includes the majority of palm species, which have growth and reproduction activities increasing linearly with plant size, during all life cycle (Piñero & Sarukhán 1982, Oyama 1990, Enright 1992, Mendoza & Franco 1998, Svenning 2000, Berry & Gorchov 2004. In this case, senescence may be expressed by the collapse of the tissues holding the stem (Crawley 1997) causing the mortality of the individual.…”
Section: Introductionmentioning
confidence: 99%